(untitled) (Research, Society and Development, 2023)
Neonatal severe is a disease in which the baby acquires hyperthyroidism due to the transfer of thyroid-stimulating antibodies from the mother to the fetus during pregnancy. Because it is rare, expresses high morbidity and mortality and does not always present accurate diagnosis and treatment, it has been widely explained. This study aimed to identify the main problems arising from the pathology known as neonatal Graves for the mother-child binomial, as well as verify the main and most recent data on its diagnosis and treatment presented in the literature. This is an integrative, qualitative and descriptive review article. The databases used were: PubMed, EMBASE and Scielo. The inclusion criteria were: articles published between 2013 and 2023, in Portuguese, English or Spanish, available free of charge in full. The exclusion criteria were: duplicate works, which do not present at least two of the descriptors in the abstract or title. We can see that the main diagnoses concern: clinical assessment, correct dosage of thyroid hormones, TSH dosage, ultrasound, scintigraphy and monitoring the development of symptoms. Regarding the main treatments reported, the main ones were: supportive treatment, antithyroid drugs, radioactive iodine, beta-blockers and, in very rare cases, surgical treatment. Although the best ones are still a subject of discussion, the main diagnoses involve clinical and biochemical evaluation, fetal diagnosis during prenatal care and neonatal screening. Regarding treatment, the most recommended were those that began immediately after confirmation of the disease: using antithyroid drugs (ATD) and concomitant and parallel therapeutic approaches, depending on the case.